PENGEMBANGAN TES DIAGNOSTIK UNTUK MENGIDENTIFIKASI PEMAHAMAN KONSEP SISWA SMA PADA POKOK BAHASAN GELOMBANG BUNYI - Unggul Wahyono; I Made Hermanto; Nurhayati Nurhayati; Lukman Samatowa; Wahyu Muzizat Mohamad; Ni Luh Sri Maharani (Universitas Negeri Gorontalo, 2023)
This study aims to develop a diagnostic test for understanding the concept of sound waves and to test the validity and reliability of the test. The research method used is development research with reference to the ADDIE model (Analyzing, Designing, Developing, Implementing, Evaluating). This research was conducted at a senior high school in the city of Bandung involving 30 students as respondents. The stages of developing a diagnostic test include literature study, needs analysis, formulating competencies and indicators, developing test items, expert validation, test trials, reliability analysis, ease of analysis, discriminating power analysis, and item selection. The validity of the diagnostic test for understanding the concept of sound waves was tested using several techniques, such as content validation and construct validation. While the reliability of the diagnostic test was tested using the K-R.20 calculation. The results showed that the developed diagnostic test for understanding the concept of sound waves had good validity and reliability. This test can be used to measure students' understanding of the concept of sound waves and to identify difficulties experienced by students in understanding the concept.